Preform for carbon-carbon composite material or carbon-ceramic composite material, carbon-carbon composite material, carbon-ceramic composite material and preparation method thereof
By adopting a three-dimensional annular needle-punching prefabricated body with a weft-free fabric ring layer and a mesh ring layer, and performing carbon enhancement, high-temperature graphitization and silicon permeation processes, the problem of insufficient bond strength and thermal conductivity between the existing carbon-carbon composite materials and carbon ceramic materials is solved, and high-performance carbon-carbon composite materials or carbon ceramic materials are achieved.
Patent Information
- Application Number
- CN202510072529.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-29
AI Technical Summary
The interlayer bonding strength and thermal conductivity of existing carbon-carbon composite materials and carbon ceramic materials are weak, making it difficult to meet the performance requirements in complex brake environments, and there is a risk of overload, overheating or even breaking, posing a safety hazard.
A prefabricated body for carbon-carbon composite or carbon ceramic material is adopted, which includes a hollow part and a radially outwardly formed circulation unit. Each circulation unit includes a weft-free ring layer and a mesh ring layer. The angle between the carbon fiber bundle and the radial plane of the prefabricated body is greater than 0° or less than 90°. A three-dimensional annular needle-punched prefabricated body is formed through the circulation laying and needle-punching process, and a high-performance carbon-carbon composite or carbon ceramic material is prepared by carbon-increasing, high-temperature graphitization and silicon permeation processes.
It significantly improves the interlayer shear strength and thermal conductivity of carbon-carbon composite materials or carbon ceramic materials, meets the performance requirements in complex brake environments, reduces the production cost of materials, and improves the utilization rate of materials.
Smart Images

Figure CN119899039A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of carbon-carbon composite materials and carbon ceramic materials, and more specifically to a preform structure of a carbon-carbon composite material or a carbon ceramic material and a preparation method of the preform, the carbon-carbon composite material and the carbon ceramic material. Background Art
[0002] Carbon-carbon composites and carbon-ceramic composites, as a new type of composite materials, have the advantages of lower density, more stable friction coefficient, higher thermal conductivity and longer service life than traditional metal materials. They have broad application prospects in the fields of automobiles, airplanes, high-speed train brake pads or brake discs.
[0003] Taking carbon ceramic brake discs as an example, they can be divided into short fiber molded carbon ceramic brake discs and long fiber carbon ceramic brake discs. Short fiber molded carbon ceramic brake discs are made by chopping carbon fibers and mixing them with resin, then hot pressing and curing them in a mold to prepare a short fiber molded carbon embryo, which is then siliconized. Long fiber carbon ceramic brake discs are made by needle-punching long carbon fibers to form a three-dimensional needle-punched preform, which is then densified by liquid phase impregnation carbonization or chemical vapor deposition (CVI) and then siliconized.
[0004] However, since the layers of short-fiber molded carbon ceramic brake discs are connected by short fibers, and the layers of long-fiber carbon ceramic brake discs are connected by needle-punched fibers, the interlayer bonding strength of these two types of brake discs is relatively weak and their thermal conductivity is relatively poor. Under extreme conditions such as high-speed braking or long-term braking, they are prone to risks such as overload, overheating, and even breakage, thus posing a safety hazard.
[0005] Therefore, how to further improve the interlayer bonding strength and thermal conductivity of carbon-carbon composites or carbon-ceramic composites to meet the performance requirements in complex braking environments has become an urgent problem to be solved for carbon-carbon composites or carbon-ceramic composites. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a preform structure of a carbon-carbon composite material or a carbon-ceramic material and a preparation method of the preform, the carbon-carbon composite material and the carbon-ceramic material to solve the problems raised in the background technology.
[0007] In order to achieve the above-mentioned purpose, the present invention proposes a preform for a carbon-carbon composite material or a carbon-ceramic composite material, which includes a hollow portion and at least one circulation unit formed radially outward from the hollow portion, each of the circulation units includes at least one layer of a non-weft cloth ring layer and a mesh tire ring layer arranged radially from the inside to the outside; wherein the angle between the carbon fiber bundle in the non-weft cloth layer and the radial plane of the preform is greater than 0° and less than or equal to 90°.
[0008] In some embodiments, the carbon fiber bundles in the same layer of weft-free cloth loop layer have the same orientation, and the angle between the carbon fiber bundles in two adjacent layers of weft-free cloth loop layers is greater than or equal to 0° and less than or equal to 90°.
[0009] In some embodiments, the angle between the carbon fiber bundles in the weft-free fabric loop layer in the circulation unit and the radial plane of the preform gradually increases along the radial direction.
[0010] In some embodiments, the number of layers of the non-weft cloth ring layer in each of the circulation units is two to four layers; the carbon fiber of the non-weft cloth layer includes but is not limited to one or more of polyacrylonitrile-based carbon fiber, viscose-based carbon fiber and asphalt-based carbon fiber; the carbon fiber of the web layer in the three-dimensional annular needle-punched preform includes but is not limited to one or more of polyacrylonitrile-based carbon fiber, viscose-based carbon fiber and asphalt-based carbon fiber.
[0011] In some embodiments, the thickness of the preform is 3 to 500 mm, and the bulk density is 0.3 to 0.7 g / cm 3 .
[0012] Some other embodiments of the present application provide a preparation method for preparing any of the above-mentioned carbon-carbon composite materials or carbon-ceramic composite material preforms, which comprises: sequentially cyclically stacking a non-woven fabric layer and a mesh layer on a rolling core to form a plurality of cyclic units consisting of the non-woven fabric ring layer and the mesh layer ring layer, and after each layer of the mesh layer is laid, a round screen needle punching machine is used for acupuncture; the acupuncture density is 20 to 60 needles / cm 2 The acupuncture depth is 6 to 10 mm.
[0013] Some other embodiments of the present application provide a method for preparing a carbon-carbon composite material, which uses any of the carbon-carbon composite materials or carbon-ceramic composite material preforms described above and is prepared by carbonization and high-temperature graphitization processes; the carbonization process is not limited to one or more of a liquid phase impregnation carbonization process and a chemical vapor deposition process; wherein the carbon source used in the liquid phase impregnation carbonization process is not limited to one or more of an unsaturated polyester resin, an epoxy resin, a phenolic resin, a melamine formaldehyde resin, and a furan resin; the carbonization temperature The temperature is 550-1000°C, the holding time is 0.5-24h, and the protective gas includes one or more of argon, helium, and nitrogen; wherein the carbon source used in the chemical vapor deposition process includes but is not limited to one or more of methane, ethylene, and propyne; the temperature of the chemical vapor deposition process is 850-1150°C, and the holding time is 200-400h; the temperature of the high-temperature graphitization is 1500-2500°C, and the holding time is 3-8h, and protective gases including but not limited to nitrogen, argon, etc. are used.
[0014] Some other embodiments of the present application provide a carbon-carbon composite material, which is prepared by the above method, wherein the bulk density of the carbon-carbon composite material is 1.0 to 1.8 g / cm 3 , thickness is 3~500mm.
[0015] Some other embodiments of the present application propose a method for preparing a carbon-ceramic composite material, characterized in that it uses any one of the above-mentioned carbon-carbon composite materials or carbon-ceramic composite material preforms, and is prepared by carbonization, high-temperature graphitization and siliconization processes; wherein the carbonization process includes but is not limited to one or more of a liquid phase impregnation carbonization process and a chemical vapor deposition process; the carbon source used in the liquid phase impregnation carbonization process includes but is not limited to one or more of an unsaturated polyester resin, an epoxy resin, a phenolic resin, a melamine formaldehyde resin, and a furan resin; the carbonization temperature is 550°C to 1000°C, the insulation time is 0.5h to 24h, and the protective gas is The carbon source used in the chemical vapor deposition process includes but is not limited to one or more of methane, ethylene, and propyne; the temperature of the chemical vapor deposition process is 850-1150°C, and the holding time is 200-400h; the temperature of the high-temperature graphitization is 1500-2500°C, and the holding time is 3-8h, using protective gases including but not limited to nitrogen, argon, etc.; the siliconization process includes but is not limited to one or more of chemical vapor siliconization (CVI), reactive melt infiltration (RMI), precursor impregnation pyrolysis (PIP) and liquid silicon infiltration (LSI).
[0016] Some other embodiments of the present application provide a carbon-ceramic composite material, which is prepared by the above method, wherein the carbon-ceramic composite material has a thickness of 3 to 500 mm and a bulk density of 1.5 to 3.0 g / cm 3 .
[0017] The preform of the carbon-carbon composite material or carbon-ceramic composite material and the corresponding carbon-carbon composite material and carbon-ceramic composite material of the present invention have higher interlaminar shear strength and thermal conductivity, and also have higher material utilization rate and lower production cost.
[0018] Description of the attached figures and tables
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings and appendices required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0020] Figure 1It is a schematic diagram of the three-dimensional structure of a carbon-carbon composite material or carbon-ceramic composite material preform according to an embodiment of the present invention.
[0021] Figure 2 It is a schematic diagram of the top view structure and a schematic diagram of the microstructure of a carbon-carbon composite material or carbon-ceramic composite material preform according to an embodiment of the present invention.
[0022] Figure 3 for Figure 2 Enlarged schematic diagram of part D in the middle.
[0023] Figure 4 A schematic diagram of the preparation process of a carbon-carbon composite material or a carbon-ceramic composite material preform, a carbon-carbon composite material, and a carbon-ceramic material according to an embodiment of the present invention; DETAILED DESCRIPTION
[0024] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] like Figure 1 , Figure 2 The preform 200 for carbon-carbon composite materials or carbon-ceramic composite materials of the embodiment of the present invention shown is also called a three-dimensional annular needle-punched preform, and its structure includes a hollow portion 210 and at least one circulation unit formed radially outward from the hollow portion, each of the circulation units includes at least one layer of non-weft cloth ring layer and mesh tire ring layer arranged radially from the inside to the outside; wherein the angle between the carbon fiber bundle in the non-weft cloth layer and the radial plane of the preform, that is, the working surface 220, is greater than 0° and less than or equal to 90°.
[0026] The preparation process of the carbon-carbon composite material or carbon ceramic material preform comprises: a plurality of circulation units are radially coated from the surface of the core 100 to the outside, each circulation unit comprises a non-woven fabric layer 202 and a web layer 203 radially coated from the inside to the outside, for example Figure 3 The non-woven fabric layers 202A, 202B and the web layers 203A, 203B are shown to form non-woven fabric loop layers and web loop layers.
[0027] The angle between the carbon fiber bundles in the non-wefted fabric layer and the radial plane of the preform is 0°<α≤90°, and the angle between the carbon fibers in two adjacent non-wefted fabric layers is 0°≤β≤90°, or 0°≤β≤45°.
[0028] The number of the non-woven fabric loop layers in each circulation unit may be at least one layer, or multiple layers, such as two layers, three layers, four layers, etc.
[0029] For example, the arrangement of the circulation structure along its radial direction may be A1B / A2B / A3B / ...... / A n B, where A1, A2, A3...A n The angle between the carbon fiber and the radial plane of the preform is 0°<α1, α2, α3, ... α n ≤90°.
[0030] For example, the arrangement of the circulation structure along its radial direction may be A1A2B / A3A4B / ...... / A n A n+1 B, A1, A2, A3...A n , A n+1 The angle between the carbon fiber and the radial plane of the preform is 0°<α1, α2, α3, ... α n , α n+1 ≤90°.
[0031] For example, the arrangement of the circulation structure along its radial direction may be A1A2A3B / A4A5A6B / ...... / A n A n+ 1A n+2 B, A1, A2, A3...A n , A n+1 , A n+2 The angle between the carbon fiber and the radial plane of the preform is 0°<α1, α2, α3, ... α n , α n+1 ,
[0032] α n+2 ≤90°.
[0033] For example, the arrangement of the circulation structure along its radial direction may be A1A2A3A4B / A5A6A7A8B / ...... / A n A n+1 A n+2 A n+3 B, A1, A2, A3...A n , A n+1 , A n+2 , A n+3 The angle between the carbon fiber and the radial plane of the preform is 0°<α1, α2, α3, ...
[0034] α n , α n+1 , α n+2 , α n+3 ≤90°.
[0035] During the coating process, a circular screen needle punching machine 300 is used to needle each of the circulation units. For example, after the web layer is coated, a needle is used to allow part of the web layer to enter the non-woven fabric layer, or to pass through the non-woven fabric layer into the adjacent web layer, such as Figure 3 The structure shown by reference numerals 231A and 231B in the figure is used to prepare the three-dimensional annular needle-punched preform. The carbon fiber without weft cloth layer in the three-dimensional annular needle-punched preform includes but is not limited to one or more of polyacrylonitrile-based carbon fiber, viscose-based carbon fiber and asphalt-based carbon fiber;
[0036] The volume density of the three-dimensional annular needle-punched carbon fiber preform formed by the above method is 0.3-0.7 g / cm 3 The acupuncture density is 20 to 60 needles / cm 2 The acupuncture depth is 6 to 10 mm. Figure 1 The innermost circle may show the mesh hoop material.
[0037] The obtained carbon-carbon composite material or carbon-ceramic composite material preform has a thickness of 3 to 500 mm and a body density of 0.3 to 0.7 g / cm 3 .
[0038] Figure 4 The complete process flow chart for preparing carbon ceramic composite materials is as follows: Figure 4 As shown, it includes:
[0039] Step S1: using the web layer and the non-woven fabric layer to prepare a three-dimensional annular needle-punched preform through a needle-punching process, that is, forming the above-mentioned three-dimensional annular needle-punched preform.
[0040] Step S2: performing a carbonization treatment on the three-dimensional annular needle-punched preform;
[0041] Step S3: performing high-temperature graphitization treatment on the three-dimensional annular needle-punched preform after the carburization treatment;
[0042] Step S4: performing siliconization treatment on the three-dimensional annular needle-punched preform after high-temperature graphitization treatment.
[0043] The carbonization treatment of the three-dimensional annular needle-punched preform in step S2 includes but is not limited to one or more of a liquid phase impregnation carbonization process and a chemical vapor deposition process. The carbon source used in the liquid phase impregnation carbonization process includes but is not limited to one or more of unsaturated polyester resin, epoxy resin, phenolic resin, melamine formaldehyde resin, and furan resin; the carbonization temperature is 550°C to 1000°C, the holding time is 0.5h to 24h, and the protective gas includes one or more of argon, helium, and nitrogen.
[0044] The carbon source used in the chemical vapor deposition (CVD) process includes but is not limited to one or more of methane, ethylene, and propyne; the temperature of the chemical vapor deposition process is 850-1150° C., and the insulation time is 200-400 hours.
[0045] In the step S3, the three-dimensional annular needle-punched preform after the carburization treatment is subjected to high-temperature graphitization. The high-temperature graphitization temperature is 1500-2500° C., the insulation time is 3-8 hours, and the protective gas includes but is not limited to nitrogen, argon, etc.
[0046] In the step S4, the three-dimensional annular needle-punched preform after high-temperature graphitization is subjected to siliconization treatment, and the siliconization process includes but is not limited to one or more of chemical vapor siliconization (CVI), reactive melt infiltration (RMI), precursor infiltration pyrolysis (PIP) and liquid silicon infiltration (LSI).
[0047] The thickness of the carbon-ceramic composite material obtained by the above process is 3-500 mm, and the bulk density of the carbon-ceramic composite material is 1.5-3.0 g / cm 3 .
[0048] By simplifying the above process and removing the final siliconizing treatment, a carbon-carbon composite material can be obtained. The thickness of the carbon-carbon composite material is 3 to 500 mm, and the body density of the carbon-carbon composite material is 1.0 to 1.8 g / cm 3 , thickness 3~500mm
[0049] The following describes the preform structure of the carbon-carbon composite material or carbon ceramic material and the preparation method of the preform, carbon-carbon composite material, and carbon ceramic material described in the technical solution of the present application in combination with specific parameters, and compares the performance differences using the prepared samples one, two, and three.
[0050] Sample 1,
[0051] First, use a flat needle punching machine to needle punch once after laying a layer of mesh layer, and control the needle punching density to 35 needles / cm 2 , the needling depth is 7mm. During the needling process, untwisted polyacrylonitrile-based long carbon fiber non-weft cloth is used as the non-weft cloth layer, and untwisted polyacrylonitrile chopped carbon fiber is used as the mesh layer, and the length of the chopped carbon fiber is 58mm. A cyclic laying method of one layer of non-weft cloth and one layer of mesh is adopted, wherein the non-weft cloth layer is laid in an alternating cycle of 0° and 90°. According to the above method, a preform with a length of 500mm, a width of 500mm, and a thickness of 35mm is prepared. Along the thickness direction of the preform, a cutting machine is used to cut it into an annular preform with an inner diameter of 155mm, an outer diameter of 400mm, and a thickness of 35mm.
[0052] The annular preform is then subjected to a carbon enhancement treatment by using a chemical vapor deposition method, using propyne as a carbon source gas, controlling the deposition temperature to be 1000° C., and the holding time to be 256 h.
[0053] The carbon-enhanced preform is then subjected to high-temperature graphitization treatment, using nitrogen as the protective gas, controlling the graphitization temperature to 1800°C, and holding time to 5 hours. After completion, the graphitized preform is taken out.
[0054] The graphitized preform is siliconized by a reaction melting method, and after completion, the siliconized brake disc is finely processed according to the drawings.
[0055] Sample 2
[0056] First, use a rotary screen needle punching machine to needle punch once after laying a layer of mesh, and control the needle punching density to 35 needles / cm 2 , the needling depth is 7mm. During the needling process, untwisted polyacrylonitrile-based long carbon fiber non-weft cloth is used as the non-weft cloth layer, and untwisted polyacrylonitrile short carbon fiber is used as the mesh layer, and the length of the short carbon fiber is 58mm. A cyclic layering method of one layer of non-weft cloth and one layer of mesh is adopted, wherein the angle between the carbon fiber in the non-weft cloth layer and the radial plane of the preform is 180°. According to the above method, a ring-shaped preform with an inner diameter of 155mm, an outer diameter of 400mm, and a thickness of 35mm is prepared.
[0057] The annular preform is then subjected to a carbon enhancement treatment by using a chemical vapor deposition method, using propyne as a carbon source gas, controlling the deposition temperature to be 1000° C., and the holding time to be 256 h.
[0058] The carbon-enhanced preform is subjected to high-temperature graphitization treatment, using nitrogen as a protective gas, controlling the graphitization temperature to be 1800° C., and holding time to be 5 hours. After completion, the graphitized preform is taken out.
[0059] The graphitized preform is then siliconized by a reaction melting method, and after completion, the siliconized brake disc is finely processed according to the drawings.
[0060] Sample 3
[0061] First, use a rotary screen needle punching machine to needle punch once after laying a layer of mesh, and control the needle punching density to 35 needles / cm 2, the needling depth is 7mm. During the needling process, untwisted polyacrylonitrile-based long carbon fiber non-weft cloth is used as the non-weft cloth layer, and untwisted polyacrylonitrile short carbon fiber is used as the mesh layer, and the length of the short carbon fiber is 58mm. A cyclic laying method of one layer of non-weft cloth and one layer of mesh is adopted, wherein the angle between the carbon fiber bundle in the non-weft cloth layer and the radial plane of the preform is 45°, and the angle between the carbon fiber bundle in the adjacent non-weft cloth layer is 90°. According to the above method, a ring-shaped preform with an inner diameter of 155mm, an outer diameter of 400mm, and a thickness of 35mm is prepared.
[0062] The annular preform is then subjected to a carbon enhancement treatment by using a chemical vapor deposition method, using propyne as a carbon source gas, controlling the deposition temperature to be 1000° C., and the holding time to be 256 h.
[0063] The carbon-enhanced preform is then subjected to high-temperature graphitization treatment, using nitrogen as a protective gas, controlling the graphitization temperature to be 1800° C., and holding time to be 5 hours. After completion, the graphitized preform is taken out.
[0064] The graphitized preform is then siliconized by a reaction melting method, and after completion, the siliconized brake disc is finely processed according to the drawings.
[0065] Table 1 is a comparison of performance data of the embodiments of the present invention.
[0066] index unit Sample 1 Sample 2 Sample 3 thickness mm 35 35 35 Inner radius mm 155 155 155 Outer radius mm 400 400 400 Body density <![CDATA[g / cm 3 ]]> 2.3 2.3 2.3 α angle ° 180 90 45 β angle ° 90 0 90 Thermal conductivity W / (m·K) 45 62 56 Interlaminar shear strength MPa 15 32 26 Material utilization % 43.18 100 100
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A preform for a carbon-carbon composite material or a carbon-ceramic composite material, characterized in that: It includes a hollow portion and at least one circulation unit formed radially outward from the hollow portion, each of the circulation units includes at least one layer of weft-free cloth ring layer and mesh tire ring layer arranged radially from the inside to the outside; wherein the angle between the carbon fiber bundle in the weft-free cloth layer and the radial plane of the preform is greater than 0° and less than or equal to 90°.
2. The preform for carbon-carbon composite material or carbon-ceramic composite material according to claim 1, characterized in that: The carbon fiber bundles in the same weft-free cloth loop layer have the same orientation, and the angle between the carbon fiber bundles in two adjacent weft-free cloth loop layers is greater than or equal to 0° and less than or equal to 90°.
3. The preform for carbon-carbon composite material or carbon-ceramic composite material according to claim 2, characterized in that: in, The angle between the carbon fiber bundles in the weft-free cloth ring layer in the circulation unit and the radial plane of the preform gradually increases along the radial direction.
4. The preform for carbon-carbon composite material or carbon-ceramic composite material according to claim 2, characterized in that: The number of layers of the non-weft cloth ring layer in each of the circulation units is two to four; the carbon fiber of the non-weft cloth layer includes but is not limited to one or more of polyacrylonitrile-based carbon fiber, viscose-based carbon fiber and asphalt-based carbon fiber; the carbon fiber of the web layer in the three-dimensional annular needle-punched preform includes but is not limited to one or more of polyacrylonitrile-based carbon fiber, viscose-based carbon fiber and asphalt-based carbon fiber.
5. The preform of the carbon-carbon composite material or carbon-ceramic composite material according to claim 1, characterized in that: The thickness of the preform is 3-500 mm, and the body density is 0.3-0.7 g / cm 3 .
6. A method for preparing a carbon-carbon composite material or a carbon-ceramic composite material preform as claimed in any one of claims 1 to 5, characterized in that: include: The non-woven fabric layer and the mesh layer are sequentially and cyclically stacked on the rolling core to form a plurality of cyclic units consisting of the non-woven fabric ring layer and the mesh layer ring layer, and a round screen needle punching machine is used for acupuncture after each layer of the mesh layer is laid; the acupuncture density is 20 to 60 needles / cm 2 The acupuncture depth is 6 to 10 mm.
7. A method for preparing a carbon-carbon composite material, characterized in that: A carbon-carbon composite material or carbon-ceramic composite material preform as claimed in any one of claims 1 to 5, prepared by carbonization and high-temperature graphitization process; The carbonization process includes but is not limited to one or more of a liquid phase impregnation carbonization process and a chemical vapor deposition process; The carbon source used in the liquid phase impregnation carbonization process includes, but is not limited to, one or more of unsaturated polyester resin, epoxy resin, phenolic resin, melamine formaldehyde resin, and furan resin; the carbonization temperature is 550° C. to 1000° C., the holding time is 0.5 h to 24 h, and the protective gas includes one or more of argon, helium, and nitrogen; The carbon source used in the chemical vapor deposition process includes but is not limited to one or more of methane, ethylene, and propyne; the temperature of the chemical vapor deposition process is 850 to 1150° C., and the holding time is 200 to 400 hours; The temperature of the high temperature graphitization is 1500-2500° C., the insulation time is 3-8 hours, and the protective gas includes but is not limited to nitrogen, argon, etc.
8. A carbon-carbon composite material, characterized in that: Prepared by the method of claim 7, wherein the bulk density of the carbon-carbon composite material is 1.0 to 1.8 g / cm 3 , thickness is 3~500mm.
9. A method for preparing a carbon-ceramic composite material, characterized in that: A carbon-carbon composite material or carbon-ceramic composite material preform as described in any one of claims 1 to 5 is used and prepared by carbonization, high-temperature graphitization and siliconization processes; wherein the carbonization process includes but is not limited to one or more of a liquid phase impregnation carbonization process and a chemical vapor deposition process; The carbon source used in the liquid phase impregnation carbonization process includes, but is not limited to, one or more of unsaturated polyester resin, epoxy resin, phenolic resin, melamine formaldehyde resin, and furan resin; the carbonization temperature is 550° C. to 1000° C., the holding time is 0.5 h to 24 h, and the protective gas includes one or more of argon, helium, and nitrogen; The carbon source used in the chemical vapor deposition process includes but is not limited to one or more of methane, ethylene, and propyne; the temperature of the chemical vapor deposition process is 850 to 1150° C., and the holding time is 200 to 400 hours; The temperature of high temperature graphitization is 1500-2500°C, the holding time is 3-8h, and the protective gas includes but is not limited to nitrogen, argon, etc.; The siliconizing process includes but is not limited to one or more of chemical vapor siliconizing (CVI), reactive melt infiltration (RMI), precursor infiltration pyrolysis (PIP) and liquid silicon infiltration (LSI).
10. A carbon-ceramic composite material, characterized in that: Prepared by the method of claim 9, wherein the carbon-ceramic composite material has a thickness of 3 to 500 mm and a bulk density of 1.5 to 3.0 g / cm 3 .